Single-step Cross-flow Ultrafiltration For Recovery And Purification Of Surfactin Produced By Bacillus Subtilis Atcc 21332 - Muhammad Qadri Effendy Mubarak; Mohd Hafez Mohd Isa; Abdul Rahman Hassan (International Conference on Chemical, Environment, 2024)
International Conference on Chemical, Environment & Biological Sciences (CEBS-2014) Sept. 17-18, 2014 Kuala Lumpur (Malaysia)